Job Insecurity Dan Turnover Intention Pada Karyawan Perusahaan Manufaktur Di Kota Padang - Aini Andra, Syaadatul Dara; Rahmi, Tuti (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2023)
The research aims to know how Job Insecurity deals with the turnover dealing in PT. X. employees USES a quantitative approach. Data retrieval techniques using random sampling techniques and procured as many as 216 responders. Data analysis is a simple linear regression analysis with the help of a SPSS sofware 20. After an analysis can be known if its significance is of 0,000 < 0.05 which has an f value of 36,820, then it can be said that the turnover intention rate in PT. X medium. Job Insecurity employees of PT. X also belongs to the medium category. This is in line with expert theories that provide information if Job Insecurity is an aspect that affects turnover intention. Job Insecurity has a positive contribution to turnover intention